2010
DOI: 10.1038/ejhg.2010.151
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Y-chromosome subdeletion gr/gr with the prevalence of Y-chromosome haplogroups in infertile patients

Abstract: Microdeletions in azoospermia factor (AZF) region on distal Yq are associated with male infertility and spermatogenic failure due to intra-chromosomal homologous recombination between large nearly identical repeat amplicons and are found in B10% of azoospermic and severe oligozoospermic cases. Although AZFc is deleted in azoospermia or oligozoospermia, no definitive conclusion has been drawn for the role of partial AZFc deletions to spermatogenic failure. Therefore, this study is planned to investigate the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 40 publications
4
51
3
Order By: Relevance
“…Amongst these, the frequency of gr/gr but not b1/b3 and b2/b3 deletions was significantly higher in men with azoospermia or oligozoospermia as compared to fertile controls, none of the individuals had b2/b4 deletions. This data is in agreement with previous studies in Indian population wherein gr/gr but not b2/b3 was found to be significantly higher in infertile men as compared to controls [34]. The involvement of b1/b3 is yet controversial.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Amongst these, the frequency of gr/gr but not b1/b3 and b2/b3 deletions was significantly higher in men with azoospermia or oligozoospermia as compared to fertile controls, none of the individuals had b2/b4 deletions. This data is in agreement with previous studies in Indian population wherein gr/gr but not b2/b3 was found to be significantly higher in infertile men as compared to controls [34]. The involvement of b1/b3 is yet controversial.…”
Section: Discussionsupporting
confidence: 93%
“…The involvement of b1/b3 is yet controversial. In the present study and that reported recently [35], b1/b3 deletions were not found to be associated with male infertility; however, Shahid et al [34] found a significantly higher numbers of infertile subjects with b1/b3 deletions. At present, the reason for such discrepant findings is unknown; to rule out an effect of sample numbers, we pooled the data from all the three studies and analysed the data statistically.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations